Design of the Interactive Activity Book “Let's Brush Our Teeth!” as an Innovative Approach to Dental Health Education for Children Aged 2–6 in Collaboration with Fransiskus Leo Dental Clinic in Medan - Katherine Tanada; Muhammad Fikri Akbar Zuhdi; Elis Savitri (Sean Institute, 2026)
Dental health problems in early childhood remain relatively high, especially among children aged 2-6 years, indicating a low level of awareness about the importance of maintaining oral hygiene from an early age. At this stage, children tend to learn more effectively through visual media and play-based activities, making interactive and engaging educational media essential. This study aims to design an interactive activity book as a learning medium for dental health that is appropriate for early childhood characteristics. The method used is design thinking, which consists of empathize, define, ideate, prototype, and test stages. The result of this study is an interactive book featuring cartoon illustrations, bright colors, and various interactive elements such as flaps, sliding, pull tabs, and matching activities. This book not only helps children understand the importance of dental care but also encourages parental involvement in the learning process. The testing results show that this media can increase children’s interest and engagement in learning. Therefore, this interactive activity book can serve as an effective alternative educational medium to support the development of good dental care habits from an early age.